2023
DOI: 10.3390/biomedicines11041047
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics Approaches toward Precision Medicine for Idiopathic Pulmonary Fibrosis: Focus on DNA Methylation

Abstract: Genetic information is not transmitted solely by DNA but by the epigenetics process. Epigenetics describes molecular missing link pathways that could bridge the gap between the genetic background and environmental risk factors that contribute to the pathogenesis of pulmonary fibrosis. Specific epigenetic patterns, especially DNA methylation, histone modifications, long non-coding, and microRNA (miRNAs), affect the endophenotypes underlying the development of idiopathic pulmonary fibrosis (IPF). Among all the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 147 publications
(161 reference statements)
1
3
0
Order By: Relevance
“…In addition to D f , our study also investigated the relationship between FF density and disease progression in IPF. FFs are aggregates of activated fibroblasts that are thought to play a key role in the pathogenesis of IPF by driving aberrant tissue remodeling [24][25][26]. Our finding of a significant correlation between FF density and D f is consistent with previous studies that have shown that FFs are a strong predictor of disease progression in IPF [14,27,28].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to D f , our study also investigated the relationship between FF density and disease progression in IPF. FFs are aggregates of activated fibroblasts that are thought to play a key role in the pathogenesis of IPF by driving aberrant tissue remodeling [24][25][26]. Our finding of a significant correlation between FF density and D f is consistent with previous studies that have shown that FFs are a strong predictor of disease progression in IPF [14,27,28].…”
Section: Discussionsupporting
confidence: 90%
“…According to certain recent studies, epigenetic control of structural and immunological cells within wounds may affect the healing process and cell phenotypes in individuals with diabetes [ 11 ]. Epigenetics will help with precision medicine approaches to diabetic wound healing [ 12 , 13 ]. Epigenetics is the study of non-heritable and heritable genetic coding [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in DNMT activity due to H 2 S dysregulation have been associated with altered DNA methylation patterns in neurons, contributing to the aberrant gene expression observed in NDs. For instance, H 2 S-mediated changes in DNA methylation have been linked to the dysregulation of genes involved in neuroinflammation, oxidative stress, and neuronal survival [ 70 , 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%